2020
DOI: 10.1136/bmjopen-2020-039722
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ and managers’ knowledge, attitudes and perceptions regarding international medical volunteering in Uganda: a qualitative study

Abstract: ObjectivesThe study sought to explore the knowledge, attitudes and perceptions of healthcare providers and health programme managers regarding the benefits, challenges and impact of international medical volunteers’ clinical placements. Views on how to better improve the work of international medical volunteers and the volunteer organisation Voluntary Service Overseas (VSO) for the benefit of local communities were also explored.SettingsPublic healthcare facilities, VSO offices in Gulu and VSO offices in Kampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…A recent study explored the views of local Ugandan healthcare providers who had worked alongside international medical volunteers during 1-year clinical placements with Voluntary Services Overseas, and reported beneficial impacts of volunteers (clinical service provision, multidisciplinary teamwork, patient-centred care, implementation of audits, improved quality of care, clinical teaching and mentoring for local healthcare providers); identified challenges of working with volunteers (language barriers and unrealistic expectations) and the organisation (lack of clear communication and feedback processes); and provided recommendations to improve volunteer placements and working partnership with the organisation (more local stakeholder input and longer placements). 35 Similar to our study, local Ugandan healthcare providers were overall positive regarding international medical volunteering and recommended that healthcare providers from other countries are Open access enabled to volunteer in such settings if resources are available to do so. 35 Meaning of the study Medical volunteers from the UK and from LMICs, reported that they could transfer new skills to their workplace, having gained more confidence to become trainers for other courses, and further develop teaching skills.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…A recent study explored the views of local Ugandan healthcare providers who had worked alongside international medical volunteers during 1-year clinical placements with Voluntary Services Overseas, and reported beneficial impacts of volunteers (clinical service provision, multidisciplinary teamwork, patient-centred care, implementation of audits, improved quality of care, clinical teaching and mentoring for local healthcare providers); identified challenges of working with volunteers (language barriers and unrealistic expectations) and the organisation (lack of clear communication and feedback processes); and provided recommendations to improve volunteer placements and working partnership with the organisation (more local stakeholder input and longer placements). 35 Similar to our study, local Ugandan healthcare providers were overall positive regarding international medical volunteering and recommended that healthcare providers from other countries are Open access enabled to volunteer in such settings if resources are available to do so. 35 Meaning of the study Medical volunteers from the UK and from LMICs, reported that they could transfer new skills to their workplace, having gained more confidence to become trainers for other courses, and further develop teaching skills.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 79%
“…35 Similar to our study, local Ugandan healthcare providers were overall positive regarding international medical volunteering and recommended that healthcare providers from other countries are Open access enabled to volunteer in such settings if resources are available to do so. 35 Meaning of the study Medical volunteers from the UK and from LMICs, reported that they could transfer new skills to their workplace, having gained more confidence to become trainers for other courses, and further develop teaching skills. An increase in leadership and management skills was also considered very useful and of benefit for the home country setting as was also described in other reports.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 79%
“…There are many significant advantages to volunteering, including helping provide more services and clinical care, reducing the workload for local staff, improving the quality of care, and shortening waiting times for patients. In return, it enhances how the community views and uses health care services [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In that case, it may be better to operate on the indigent population which isn't taking away from the paying patients of local doctors. 18 At a minimum, bias training should be considered as part of pre-trip planning and ongoing team development. Getting to know colleagues with different backgrounds and experiences and building friendships with surgeons who don't look like you may be the most impactful to begin breaking down barriers.…”
Section: Guru Saysmentioning
confidence: 99%